Understanding Ankle Pumping Exercises for Elderly People with Diabetic Foot Ulcers at the Cisadea Community Health Center, Malang: Pemahaman Latihan Ankle Pumping Pada Lansia Penderita Diabetic Foot Ulcer Di Puskesmas Cisadea Malang - Agum Pradhika Firlanna; Anita Faradilla Rahim; Doni Oktavianto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Diabetes Mellitus (DM) is a disease that has been around for a long time. There are often high blood sugar levels and intolerance to sugar substitutes, because the pancreas gland cannot produce sufficient insulin, the body cannot use the insulin produced normally, or both. There are several risk factors that follow, such as peripheral arterial disease, neuropathy, the immune system, and continuous internal or external trauma. This trauma will give rise to infection and then the formation of an open wound which is often called Diabetic Foot Ulcer (DFU). This DFU can cause several disorders such as decreased muscle flexibility and range of motion of the ankle joint. The aim of this outreach is to provide education and ankle pumping exercises to elderly people with DFU which can be done independently at home. The results obtained were an increase in public insight and knowledge regarding ankle pumping exercises, and regarding the prevention of DFU. The targeted elderly with DFU understand and can do ankle pumping exercises regularly, obediently and independently without the help of other people at home. Before counseling, the elderly understood DM and DFU better than prevention and ankle pumping exercises, indicating that healing behavior is better known than prevention. This shows the need for follow-up activities in the form of intensifying health promotion activities, especially for preventive measures.